(untitled) (Bangladesh Journal of Medical Science, 2022)
Subjective Visual Vertical test (SVVT) is an assessment that we can do to rule out vestibular function status specifically the function of the utricle in the inner ear. The purposes of this test are to assess the perception of verticality or to detect abnormal subjective tilt. In normal persons, the ability to perceive verticality is quite good. This ability depends on input from visual, vestibular, and somatosensory systems. Both utricle and saccule contribute to the sense of verticality and horizontality. This study aimed to compare the clockwise and counterclockwise conditions for BAL EXzz SVVT findings among healthy adults aged 18 to 35 years (mean age of 23.10 years). This was a repeated measures study that recruited 30 healthy adults (50% were males and 50% were females). After undergoing screening by using Malay Version Vertigo Symptom Scale (MVVSS), the participants underwent BAL EXzz SVVT testing using bucket method for the clockwise condition and then proceed with the counterclockwise condition. The SVVT was carried out according to the standard protocol and three measurements were made on the clockwise direction and three on the counterclockwise direction. The examiner selected the starting point, the subject then rotated the bucket and it stopped when the subject considered the line reached the vertical position. The results showed that there is statistically significant difference between clockwise and counter clockwise readings (p<0.05). However, there is no significant correlation between clockwise and counterclockwise conditions. In conclusion, BAL EXzz SVVT is a quick, non-invasive, and extremely reliable test to evaluate the structural and function of the utricle and saccule. SVV test can be measured with both clockwise and counterclockwise conditions. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 243-248